(untitled) (KULT_online, 2018)
By looking at the developments in Yugoslav culture during the 1960s through the conceptual lens of ‘Americanization’, this book shows that, despite its socialist socio-political setup, Yugoslav society underwent a profound transformation that had a distinctly American prefix, eventually producing a decidedly Americanized socialist youth. The relatively unrestrained import of American cultural products to Yugoslavia proved to be a win-win situation for both American and Yugoslav regimes. While Washington kept Tito a safe distance from the USSR, Yugoslav communists fostered their population’s sense of freedom and superiority over other socialist societies, as well as the desired external image of ‘socialism with human face’. Through its methodological symbiosis of cultural, diplomatic and history of everyday life analysis, the book offers a welcome enrichment for the research on cultural diplomacy and Cold War Studies, further advancing the scholarly ’thirding’ of Cold War dichotomies.